"The Influence of Product Quality, Price Level and Promotion on Purchasing Decision Making (Case Study on Cozy Burger Customers in Pangkajene District, Pangkep Regency )" - Akhmad, Nurul Atikah; Akib, Haedar; S, Muh Rizal (Pinisi Business Administration Review, 2022)
This study aims to determine and analyze the influence of product quality, price level and promotion on purchasing decisions of consumers of Cozy Burger business in Pangkajene District, Pangkep Regency . The research method used is a quantitative method with data collection methods, namely through observation, questionnaires and documentation. The number of samples in this study was 100 respondents from Cozy Burger business customers in Pangkajene District then analyzed using multiple linear regression analysis can be shown by the regression equation Y = 7,780 + 0.290 X1 + 0.129 X2 + 0.283 X3 from the regression equation it is known that product quality, price level, and promotion have a positive influence on purchasing decisions. The calculation result of the determination coefficient is 0.385. This shows that product quality, price level, and promotion are able to explain purchasing decisions by 38.5%. While the remaining 61.5% is explained by other variables that are not observed. Based on the results of the study, it shows that the testing conducted on the Cozy Burger business in Pangkajene District, Pangkep Regency simultaneously, the three variables (X) have a significant influence together on increasing consumer purchasing decisions for Cozy Burger (Y). Based on the partial significance test, the product quality variables ( X1 ), price level (X2 ) and promotion (X3 ) have a significant influence on increasing consumer purchasing decisions (Y).